1997
DOI: 10.1080/009841097160113
|View full text |Cite
|
Sign up to set email alerts
|

Mercury Content in Skin-Lightening Creams and Potential Hazards to the Health of Saudi Women

Abstract: It seems evident from a wealth of scientific research that mercury is toxic. Because of the nature of the Saudi markets, different brands of skin-lightening creams are widely available. In this study, 38 skin-lightening cream samples were collected and analyzed for mercury by inductively coupled plasma spectrometry after an acid digestion procedure. About 45% of the tested skin-lightening cream samples contained mercury at levels well above the FDA's acceptable limit of 1 ppm. These findings are alarming and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…The mercury level in the three categories of samples in cosmetics eye shadows, was higher than allowed and not safe and this varies with the Food and Drug of Saudi Arabia (Nill). According to the US Food and Drugs Administration (FDA), cosmetic products should not contain mercury as an ingredient (FDA) < 1 mg/kg [36,37] and agree with Al-Saleh, who reported that, mercury content was more than six times that found in other reports described in the literature [3], such as those reported by Uram et al [38].…”
Section: Resultssupporting
confidence: 78%
“…The mercury level in the three categories of samples in cosmetics eye shadows, was higher than allowed and not safe and this varies with the Food and Drug of Saudi Arabia (Nill). According to the US Food and Drugs Administration (FDA), cosmetic products should not contain mercury as an ingredient (FDA) < 1 mg/kg [36,37] and agree with Al-Saleh, who reported that, mercury content was more than six times that found in other reports described in the literature [3], such as those reported by Uram et al [38].…”
Section: Resultssupporting
confidence: 78%